(untitled) (Jurnal Manajemen Pembangunan Daerah, 2024)
ABSTRACT Poverty and income inequality are strategic social issues often faced by various regions in the Unitary State of the Republic of Indonesia, especially in newly expanded areas such as the Bangka Belitung Islands Province. One of the development issues in the Bangka Belitung Islands Province, which is included in the Regional Medium-Term Development Plan (RPJMD) 2017-2022, is related to the levels of poverty and income inequality. This research aims to analyze the factors influencing poverty and income inequality in the Bangka Belitung Islands Province using a static panel data method during the period 2007-2016. The results of this study show that economic growth has been effective in reducing the poverty rate but not in reducing income inequality. Income inequality may hinder or reduce the effectiveness of economic growth in reducing the poverty rate. Statistically, the sectors that have a positive and significant impact on reducing poverty and income inequality are the service sector and agricultural sector. The inflation rate has a negative and significant effect on the poverty rate, but the opposite effect on income inequality. Government expenditure has a positive and significant effect on reducing income inequality, but not on the poverty rate. In addition, the population has a negative and significant effect on income inequality. Keywords: Panel Data, Poverty, Income Inequality, Economic Growth